Numerical study of antireflection coatings in waveguide structures with silicon nanoparticles interlayer. Issue 4 (21st February 2017) - Ubeid, Muin F.; Shabat, Mohammed M.
Abstract: In this paper, the reflection properties of a multilayer structure containing silicon nanoparticles (Si-NPs), silicon nitride (Si3 N4 ), and silicon (Si) is investigated theoretically and numerically. The structure is arranged and its main parameters are defined. The required equations for the propagation of electromagnetic plane waves are derived in detail to obtain the reflection coefficients in a closed form. The reflected power of the structure is determined using these coefficients. In the numerical results, the mentioned power is computed and illustrated as a function of wavelength of the incident radiation, angle of incidence, and Si-NPs parameters. Optimal Si-NPs parameters (particle's diameter, space between particles, and layer thickness) for low reflection are proposed. These theoretical parameters could effectively be used to design new solar cells.